Memes: do espaço virtual à sala de aula - Vale, Lara Ferreira do (2019)
Given how widespread the access to internet became in the last decades, especially social network after the 2000s, we have seen a new type of content emerge and become viral: memes. The messages known as memes have their origins in a term coined by the biologist Richard Dawkins in 1976 and nowadays they fill in a significant amount of the contents we find in the web, from social networks such as Facebook, Instagram and Twitter, to renowned newspapers. In the face of any event of great impact, the internet bubbles with new memes that can be used, with some caution, to analyze and explain certain aspects of our society. Based on the linguists studies proposed by Luiz Antonio Marcuschi and on the semiotic studies by Lúcia Santaella, this work aims to discuss meme as a textual genre and suggests its application in the daily life of Middle, High School and University.